Pengaruh Media Tanam dan Pupuk Kompos Kotoran Sapi Terhadap Pertumbuhan Tanaman Jahe (Zingiber officinale) - Permadi, Mhd Bambang; Amrul, Hanifah Mutia Zaida Ningrum; Siswanto, Yudi (UNIVERSITAS LABUHANBATU, 2024)
Ginger contains a number of phenolic compounds that are antioxidants, which are thought to protect cells from damage. The use of organic fertilizers on agricultural land has existed since ancient times by utilizing natural materials. The advantage of cocopeat for planting media is that it can store water or maintain the humidity of the planting media. The purpose of this study was to determine the effect of providing planting media and cow dung compost and the interaction of providing planting media and cow dung compost on the growth of ginger plants (Z. officinale). This research was conducted on the land of the LLDIKTI REGION 1 SUMUT Office, Jalan Sempurna no. 8, Tanjung Sari Village, Medan Selayang District, Medan City, North Sumatra. The research time was carried out for approximately 3 months starting from March 2024 to July 2024. This study used a factorial Randomized Block Design (RAK) consisting of 2 treatment factors with 16 treatment combinations with 3 repetitions so that 48 plots were obtained with the number of plants/plot of 4 plants. So the total sample plants are 192 sample plants. Factor I is the provision of Cow Manure Compost with the symbol